Analysis of non-singular fractional bioconvection and thermal memory with generalized Mittag-Leffler kernel. (June 2022) - Asjad, Muhammad Imran; Sunthrayuth, Pongsakorn; Ikram, Muhammad Danish; Muhammad, Taseer; Alshomrani, Ali Saleh
Abstract: This paper deals with the application of non-singular fractional operator in the bioconvection flow of a MHD viscous fluid for vertical surface. The Laplace transform method is used for dimensionless governing equations of momentum, energy and diffusion respectively. Classical governing model is extended to non-integer order approach with non-singular kernel which can be used to describe the memory for natural phenomena. The main advantage is to use this fractional operator can it measure the rate of change at all points of the considered interval, therefore, the present fractional operator incorporate the previous history/memory effects of any system. For the prediction of physical behavior of embedded parameters, some graphs are presented in the graphical section. At the end some remarkable results are found. It is found that non-singular fractional operator measures the memory better in comparison with singular fractional operator. Further, on comparison between different kinds of viscous fluid (Water, Air, Kerosene), it is found that temperature and velocity of air is higher than water and kerosene respectively. The results are validated with the recent published work.